EXTENT OF UTILIZATION OF E-LEARNING RESOURCES IN BUSINESS EDUCATION PROGRAMME IN SOUTH-EAST NIGERIAN UNIVERSITIES (NAU Journal of Technology and Vocational Education, 2024)
The need to produce competentgraduates for effective performance in the global workplace necessitated this study to determine the extent of utilization ofe-learning resources in business education programme in southeast Nigerian universities. Two research questions and two hypotheses guided the study. The study adopted a descriptive survey design. The population of the study was 50 business education lecturers from the universities offering business education programme in South-EastNigeria. This population formed the sample. The instrument for data collection was a 17-item validated questionnaire developed by the researchers. The reliability of the instrument was established using Cronbach Alpha with reliability coefficients of 0.86 and 0.79 for Clusters A and B respectively. Data collected were analyzed using mean and standard deviation to answer the research questions while t-test statistic was used to test the null hypotheses at 0.05 level of significance. The results revealed that elearning resources for instructional delivery and evaluation process in business education programme in South-East Nigerian universities were utilized to a very low extent very lowly. Also, ownership of institutions did not significantly affect the opinion of business educators regarding the extent theyutilize e-learning resources for instructional delivery and evaluation process in business education programme in South-East, Nigerian universities. It was recommended among others that the university administrators in collaboration with the government should provide adequate e-learning facilities for lecturers inorder to facilitate their teaching and evaluation process.
Keywords: E-learning, E-learning resources, Business Education